The effectiveness of food safety and nutrition training programme on the preparation of safe and healthy food among handlers at primary school canteen in Kota Bharu, Kelantan - Husain, Nik Rosmawati Nik (2017)
The health and development of schoolchildren is influenced by the home and school food environment. Many efforts were conducted to improve the safety of food preparation and the healthy diet served in school canteens. However, the effectiveness of interventions are varied and rarely evaluated. This study aims to develop new intervention programme for the preparation of safe food and healthy diet among food handlers at primary school canteen in Kota Bharu, Kelantan. This study was conducted in two parts. In the Part1, 16 out of 98 primary schools were randomized into intervention and control groups using a simple random sampling. Then, 79 food handlers were selected. In Part2, 293 standard six students were recruited from the three randomly selected schools from the intervention group. The Food Safety and Nutrition Training Programme was developed based on the Theory of Planned Behaviour. On-site observations and validated questionnaires were used to collect data at the baseline and the following 6-week (Post1) and 12-week (Post2) after intervention. Results of Part1 showed that trained food handlers demonstrated significant and sustained improvement in the following: the knowledge related to personal hygiene, rules for preparing safe food, healthy food choice, and the overall knowledge of healthy diet; the self-reported practice of food safety and hygiene; and the handling of raw food and cooking equipment. Handwashing practices in thetrained group significantly increased from 29% at the baseline to 50.8% at Post1 (p=0.004). The environmental sanitation score for the intervention group was significantly increased by 13.8 points (p=0.012), and sustained up to Post2 (p=0.0168). The unsatisfactory level of Aerobic plate count, Total coliforms count, and Staphylococcus aureus from food contact surfaces were significantly reduced 20.2%, 50.4% and 27.5% respectively following the intervention. School canteens in the intervention group significantly served more vegetable menu at Post1 (p=0.040) and milk and milk products at Post2 (p=0.015) compared to the control. In Part2, compared to control group, schoolchildren in the intervention group showed significantly: higher percentage to purchase competitive foods in school canteens (49.1% vs. 47.2%), and milk and milk products (16.0% vs. 10.6%); lower percentage of students who purchased fast food (2.7% vs. 22.5%); better perception of the hygiene and sanitation of school canteens (p<0.001), and competitive foods served (p=0.001). In conclusion, the intervention was effective in improving the knowledge and behaviours of food handlers in relation to food safety and healthy diet serving in the selected primary school canteens.